An Operational Approach to Risk-Screening: Discussion - Elton, Edwin J. (Journal of Finance, 1973)
Edwin J. Elton, An Operational Approach to Risk-Screening: Discussion, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 368-369